Indonesian Shipper Event Marketing Strategy in the Shipper Sellers Series Program - Mario Philip Silalahi; Chininta Rizka Angelia; Daniel Susilo (PT FORMOSA CENDEKIA GLOBAL, 2023)
Events are a business that makes a high contribution economically, especially for developing countries. This research has a goal, which is to examine more deeply the implementation of Shipper Indonesia's event marketing strategy in the Shipper Sellers Series 2022 program. The researchers used the core concepts namely marketing communication strategy, event marketing, and brand engagement to be able to find out more about the marketing implementation of the program. This study used descriptive qualitative approach. In collecting the data, the researchers used in-depth interviews and observation. The results found that the implementation of event marketing uses several tactics including using social media such as Instagram and Facebook, working with media partners, collaborating with community partners, using well-known speakers, giving electronic money giveaways, and using social media ads. The event marketing strategy is used by Shipper Indonesia in an effort to introduce products and brands and provide experience to the public through the Shipper Sellers Series program.